54th AIAA Aerospace Sciences Meeting 2016
DOI: 10.2514/6.2016-1303
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control at Low Reynolds Numbers by Periodic Airfoil Morphing

Abstract: prepared to be submitted to the 54th AIAA Aerospace Sciences Meeting, 4-8 January 2016This paper investigates the application of a periodically deforming airfoil surface for the purpose of flow control at low Reynolds numbers. A physical model has been fabricated by bonding Macro Fiber Composite (MFC) actuators to the underside of a NACA 4415's suction surface. The results presented build on work by Jones et al.1 First, the behavior of the surface when actuated at a range frequencies is investigated through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In some of these studies, the periodic excitations were prescribed as standing waves. Jones et al [12] experimentally studied standing-wave morphing at a Reynolds number of Re = 50, 000 for a variety of temporal frequencies and angles of attack. The authors found increased velocity within the time-averaged boundary layer for certain morphing frequencies, and an associated increase in mean lift and reduction in mean drag.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, the periodic excitations were prescribed as standing waves. Jones et al [12] experimentally studied standing-wave morphing at a Reynolds number of Re = 50, 000 for a variety of temporal frequencies and angles of attack. The authors found increased velocity within the time-averaged boundary layer for certain morphing frequencies, and an associated increase in mean lift and reduction in mean drag.…”
Section: Introductionmentioning
confidence: 99%